Implementasi Motode Fuzzy Sugeno pada Pengendalian Exhoust Fan Sebagai Pembersih dan Pengatur Udara - ., Novriyenni; Pardede, Akim Manaor Hara; Hamdani, Diky (MEANS (Media Informasi Analisa dan Sistem), 2018)
In a special room for smokers, Exhoust Fan is installed to clean the air and keep the room air fresh. Most Exhoust Fan works manually, not set automatically so that it has a constant rotational speed, so the function of the exhaust fan as an air purifier is not optimal. This study aims to apply a fuzzy method as well as to control the speed of the Exhoust Fan. Fuzzy logic will process the carbon monoxide gas which is detected by the MQ-3 sensor then the output decision maker is in the form of the Exhoust Fan rotation speed level which is exactly in accordance with the amount of carbon monoxide read by the MQ3 sensor. fuzzysugeno method can regulate the speed of putan fan based on the amount of carbon monoxide read by the MQ-3 sensor.